Neuroprotective properties furan compounds GIZH-276 on the model of hemorrhagic stroke - S. A. Litvinova; N. N. Zolotov; T. A. Voronina; I. S. Kutepova; L. A. Zhmurenko (LLC "Publisher OKI", 2016)
The study of the neuroprotective properties new original compound GIZH-276 and evaluate changes activities of prolyl endopeptidase (PEP) and lactate dehydrogenase (LDH) in blood plasma of rats with post-traumatic hematoma (model of hemorrhagic stroke) is the aim of this investigation. Methodology of the study: Modeling of hemorrhagic stroke (HS) was carried out using the creation of intracerebral post-traumatic hematoma with the introduction of autologous blood into the site of injury. Assay of enzymes activities in plasma was carried out with fluorescent (PEP) and ultraviolet (LDH) methods. The results of the study: GIZH-276 at dose of 10 mg/kg (7 days, intraperitoneally) has a pronounced neuroprotective effect, attenuating neurological deficits in rats with hemorrhagic stroke 24 hours, 7 and 14 days after surgery and statistically significantly increasing the number of surviving rats by 14 days of observation. The weakening of neurological deficit and death of animals is accompanied by decreased activity of enzymes LDH and PEP, which indicates the improvement of security of brain tissue oxygen and reducing neuroinflammation. Conclusion: Safety and neuroprotective effect of GIZH-276 on the model of hemorrhagic stroke may be partially due to positive effect on inflammatory and hypoxia during the development of secondary brain damage in stroke.